Improving Communication Between Patients and Providers Using Health Information Technology and Other Quality Improvement Strategies: Focus on Low-Income Children - Ngo-Metzger, Quyen; Hayes, Gillian R.; Yunan Chen; Chen, Yunan; Cygan, Ralph; Garfield, Craig F. (Medical Care Research and Review, 2010)
Effective communication between providers and patients has been linked to improved outcomes. Previous reviews of quality improvement strategies, including health information technology (health IT), have not focused on the needs of low-income children. The authors conducted a systematic review of the literature on studies of communication surrounding the care of low-income children, with an emphasis on interventions and health IT.The search yielded six studies that focused on low-income children; three of the studies used health IT. Key informant interviews provided insight to the current use of health IT for provider—patient communication in geographically diverse, underresourced settings.The authors identify gaps between existing literature and clinical practice. Future research should focus on the specific impact of health IT in pediatric medicine, particularly in underresourced and safety net settings. These efforts should focus on the use of technological innovations to improve care for low-income children and their families.